Transformation of digital da'wah as an instrument for enhancing social welfare - Purwatiningsih, Aris Puji; Wibowo, Mochammad Eric Suryakencana; Aryani, Alvita Tyas Dwi (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - The purpose of this study was to examine how the community views digital da'wah in promoting social welfare and understanding Islamic values.Method - A purposive sampling technique will be employed to select a minimum of 200 respondents, representing diverse ages, genders, educational levels, and occupational backgrounds, to ensure representative data. The respondents will be aged 17-70 years, actively access the internet, and have education ranging from elementary school to tertiary level, using digital technology to access da'wah content.Result - The results showed that both digital and conventional da'wah play a crucial role in understanding Islamic values and enhancing social welfare.Implication – This Method suggest to to developing fresh strategies for disseminating religious messages, improving education on Islamic values, and proposing policy recommendations to enhance Muslim community involvement in digital platforms.Originality - This research exploration of the transformation of digital da'wah and its role in enhancing social welfare, as well as its influence on the perception and acceptance of the Muslim community towards digital platforms.***Tujuan - Tujuan dari penelitian ini adalah untuk mengkaji bagaimana masyarakat melihat dakwah digital dalam mempromosikan kesejahteraan sosial dan pemahaman nilai-nilai Islam.Metode - Teknik purposive sampling akan digunakan untuk memilih minimal 200 responden, yang mewakili berbagai usia, jenis kelamin, tingkat pendidikan, dan latar belakang pekerjaan, untuk memastikan data yang representatif. Responden tersebut berusia 17-70 tahun, aktif mengakses internet, dan memiliki pendidikan mulai dari sekolah dasar hingga tingkat perguruan tinggi, menggunakan teknologi digital untuk mengakses konten dakwah.Hasil - Hasil penelitian menunjukkan bahwa baik dakwah digital maupun konvensional memainkan peran penting dalam pemahaman nilai-nilai Islam dan meningkatkan kesejahteraan sosial.Implikasi - Metode ini menyarankan pengembangan strategi baru untuk menyebarkan pesan-pesan agama, meningkatkan pendidikan tentang nilai-nilai Islam, dan mengusulkan rekomendasi kebijakan untuk meningkatkan keterlibatan masyarakat Muslim dalam platform digital.Orisinalitas/Nilai - Penelitian ini merupakan eksplorasi tentang transformasi dakwah digital dan perannya dalam meningkatkan kesejahteraan sosial, serta pengaruhnya terhadap persepsi dan penerimaan masyarakat Muslim terhadap platform digital.